Evaluation of Diced Cartilage Grafts Shaped with Three-Dimensionally-Printed Bioresorbable Polycaprolactone Molds - GÜNDÜZ, OĞUZHAN; ULAĞ, SONGÜL (My University, 2022)
Copyright © 2022 by the American Society of Plastic Surgeons.BACKGROUND: The main problem with the use of diced cartilage grafts is related to the difficulties encountered in shaping the graft and unpredictible graft resorption. The aim of this study was to evaluate the permanence and viability of diced cartilage grafts shaped with the help of biodegradable, three-dimensionally-printed polycaprolactone molds. METHODS: Three groups were studied in each of the eight rabbits: block cartilage (group 1), diced cartilage (group 2), and diced cartilage shaped with polycaprolactone molds (group 3). A total of 24 cartilage grafts were obtained at the end of the 12-week follow-up period, and 10 different histopathologic parameters were analyzed in each cartilage graft. RESULTS: Diced cartilages shaped with a three-dimensionally-printed polycaprolactone mold showed increased regeneration potential of chondrocytes, vascularization, and collagen production. Use of polycaprolactone molds did not cause any additional risk of inflammation, fibrosis, or metaplastic bone formation. CONCLUSIONS: In this study, it has been shown that three-dimensionally-printed polycaprolactone molds can be used safely in shaping diced cartilage grafts. In light of this study, it will be possible to produce hybrid grafts that can be used safely in many operations such as nasal reconstruction, rhinoplasty, auricle reconstruction, and repair of orbital floor fractures with the help of molds produced in more complex ways. CLINICAL RELEVANCE STATEMENT: Three-dimensionally-printed polycaprolactone molds can be used to shape diced cartilages in the areas of both aesthetic and reconstructive surgery.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; Cerrahi; Surgery